Tingkat Pengetahuan Penggunaan Antibiotik Terhadap Resistensi - Antolin Lamsar Rogabe Samosir; Indah Laily Hilmi; Salman Salman (Journal of Pharmaceutical and Sciences, 2023)
Antibiotics are drugs used to treat bacterial acaic infections. Unreasonable use of antibiotics will cause resistance to a bacterium. I did a review of this journal aimed at analyzing the level of knowledge of antibiotic use in the community to prevent the occurrence or increase of cases of resistance to a bacterium. For the results obtained from the results of journal reviews, the level of knowledge of the average antibiotic use is still relatively up and down.